A 3D fault seal analysis study conducted in the Ibhubesi Gas Field Offshore the West Coast of South Africa - Ntombela, Nondumiso (Department of Geological Sciences, 2018)
A three dimensional fault seal analysis study of the AK fault situated offshore of the West Coast of South Africa is presented. This study is aimed at informing the development plan of the Ibhubesi gas field with regards to the compartmentalization of the reservoirs, by understanding whether a key fault, the AK fault facilitates hydrocarbon migration to the Ibhubesi field reservoirs or whether it provides a seal. In order to address this research aim, a seismic interpretation of the area was carried out and combined with an interpretation of well data to construct a 3D structural model from which the fault seal analysis was carried out. Juxtaposition analysis was used to determine the lithologies that had been juxtaposed across the fault. Fault clay was determined using the Shale Gouge Ratio (SGR) algorithm and permeability and threshold pressure were also used to quantify the fault seal capacity. The results from the SGR were correlated to the across fault pressure difference and plotted on a reference diagram which is a comparison of sealing faults vs. leaking faults. This diagram indicates that faults with an SGR greater than 25% and threshold pressures greater than 8bars, have a high potential to seal. The AK fault SGR results range between 25 and 55 % with a threshold pressure of up to 20bars. These results indicate that the AK fault is likely to be a sealing fault.